حمطات في حياة المحدث الماليزي الشيخ محمد إدريس المربوي، وآثاره العلمية - Mesbahul Hoque; Mualimin Mochammad Sahid; Muneer Ali Abdul Rab; Yuslina Mohamed (Universiti Sains Islam Malaysia, 2024)
JOHS Vol 3. No 1. June 2018